Evaluating the Multidimensional Scale of Perceived Social Support (MSPSS) in Children Aged Between 8–14 Years. - Sun, Xiaoyue; Guo, Cheng (Journal of Child & Family Studies, 2024)
Social support has been found to be crucial for children in terms of their health and daily life. The Multidimensional Scale of Perceived Social Support (MSPSS) is a self-reported scale to measure the sources of perceived social support: friends, family and significant others, which has not been previously psychometrically evaluated on children as young as 8 years old. The current study aims to examine the psychometric properties of the MSPSS in Chinese children. In total 1,482 students in Shanghai, China were recruited in the study (age range 8–14, M = 10.79, SD = 1.11). Results showed that the Cronbach's α coefficients for subscales and the total scale were all above 0.80 indicating good reliability. Confirmatory factor analysis supported the three-factor structure of the Chinese version of MSPSS. Notable ceiling effects were observed for single items and subscales, while observed floor effects were negligible. The stronger correlation found between MSPSS and the Pediatric Quality of Life Inventory (as measure of positive aspects of child life) than between MSPSS and the Strengths and Difficulties Questionnaire (as measure of negative aspects of life) yielded support for satisfying external validity. The findings lend support to the reliability and validity of the scale for assessing perceived social support on children. Highlights: Previous studies have psychometrically examined the Multidimensional Scale of Perceived Social Support in children as young as 8 years of age. A total of 1,482 Chinese children (8-14 years) with parents were recruited from a school context. A 3-factor model consisting friends, family and significant others, fit the data best. High internal consistency and satisfying external validity of the measure was found. Floor effects were negligible for all items while substantial ceiling effects were observed.